Factors Influencing the Selection of Dentistry as a Career Among Prospective Candidates: A Multicentre Cross-Sectional Study - Nor Faharina Abdul Hamid; Azlan Jaafar; Nurshafikah Nazirah Asming; Nurul Syafiqah Suria; Ting Khee Ho; Zhi Yin Joan Lim; Tong Wah Lim (Wiley, 2024)
Indexed by WOS/Scopus/ERA